GAMBARAN KEPUASAN PASIEN KANKER STADIUM LANJUT TERHADAP PERAWATAN PALIATIF DI RSUP DR. SARDJITO YOGYAKARTA - Dwi Susanti; Christantie Effendy; Sri Setiyarini (Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Patient satisfaction in palliative care is an important dimension that can describe a patient’s experience acceptable of care. Patient satisfaction is used to evaluate performance and improve the quality of palliative care. Objective: This study aimed to know the description of patient satisfaction of palliative cancer against palliative care which has been given in IRNA I RSUP Dr.Sardjito Yogyakarta based on a ranking that includes 5 subscales of satisfaction in palliative care. Method: Type of research was mixed methods with sequential explanatory design, collecting data began from collecting quantitative data and followed by collecting qualitative data. Subject of study involved cancer patient in Central Hospital of Dr. Sardjito Yogyakarta during September and October 2016 number of respondent was 48 patients and 8 participants. Sampling technique in quantitative research used purposive sampling, while the qualitative research used the techniques sampling criterion. Instrument used FAMCARE-P to measure satisfaction and the interview based on interview guideline. Quantitative data analysis used descriptive analysis and analysis of qualitative data used the content analysis. Integration of the results of quantitative research and qualitative used the joint displays. Results: Cancer patients have a high satisfaction on the subscale of support in decision-making with a mean (4,60±0,49), followed by a subscale of symptom management (3,96±0,42), communication and information (3,93±0,35), coordination and consistency (3,8±0,38) and accessibility (3,7±0,44). Qualitative research gained eight categories. Conclusion: Cancer patient satisfaction on palliative care was high with score on every subscales above mean score. Keyword: Satisfaction, Cancer Patient, Mixed Method, Palliative Care